Use of fecal occult blood test in hospitalized patients: Survey of physicians practicing in a large central Canadian health region and Canadian gastroenterologists - Ip, Stephen (Pulsus Group Inc, 2013)
BACKGROUND: Although the fecal occult blood test (FOBT) was developed for colorectal cancer screening in the outpatient setting, it continues to be used among hospitalized patients. No previous study has evaluated the knowledge, beliefs and attitudes of practicing physicians on the use of FOBT among hospitalized patients and compared practices among physicians with different medical specialty training. OBJECTIVE: To survey physicians in the Winnipeg Regional Health Authority (WRHA) and Canadian gastroenterologists (GIs) on the use of FOBT in hospitals. METHODS: A survey was distributed by e-mail to internists (n=198), emergency medicine (EM) physicians (n=118), general surgeons (n=47) and family medicine (FM) physicians with admitting privileges (n=29) in the WRHA. Canadian GIs were surveyed through the membership database of the Canadian Association of Gastroenterology (CAG) (n=449). The survey included items regarding demographics of the respondents and their current use of FOBT in hospitals. RESULTS: Response rates ranged from 18% among CAG members to 69% among FM physicians in the WRHA. General internal medicine, general surgeon and GI respondents were less likely to order a FOBT and less likely to believe that an FOBT was useful in assessing emergency room or hospitalized patients when compared with FM and EM respondents (P<0.001). The most common indications for ordering a FOBT were black stools and anemia with and without iron deficiency. Two-thirds of EM physicians preferred point-of-care testing rather than laboratory reporting of FOBT. CONCLUSIONS: The present survey suggests that FOBTs are commonly used in hospitals by EM and FM physicians for indications such as anemia and black stools.